2020
DOI: 10.3390/ma13122817
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Studies on Germanate Glasses Doped with Europium Ions for Photonic Applications

Abstract: Glass and ceramic materials doped with rare earth (RE) ions have gained wide interest in photonics as active materials for lasers, optical amplifiers, and luminescent sensors. The emission properties of RE-doped glasses depend on their chemical composition, but they can also be tailored by modifying the surrounding active ions. Typically, this is achieved through heat treatment (including continuous-wave and pulsed lasers) after establishing the ordering mechanisms in the particular glass–RE system. Within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 56 publications
(75 reference statements)
1
5
0
Order By: Relevance
“…Further studies revealed that modification of germanate glasses by P 2 O 5 allows control of their local structure and visible luminescence. The increase of P 2 O 5 content leads to the reduction of spectral linewidth and the shift of emission band of Eu 3+ ions in germanate glass to shorter wavelengths [ 23 ]. The effect of the spectroscopic properties of Tm 3+ ions for different compositions with varying Nb 2 O 5 /La 2 O 3 ratios has been studied and the optical concentration of glass components for efficient 1.8 µm near-infrared laser applications was determined [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies revealed that modification of germanate glasses by P 2 O 5 allows control of their local structure and visible luminescence. The increase of P 2 O 5 content leads to the reduction of spectral linewidth and the shift of emission band of Eu 3+ ions in germanate glass to shorter wavelengths [ 23 ]. The effect of the spectroscopic properties of Tm 3+ ions for different compositions with varying Nb 2 O 5 /La 2 O 3 ratios has been studied and the optical concentration of glass components for efficient 1.8 µm near-infrared laser applications was determined [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally known that the 5 D 0 → 7 F 1 is a magnetic dipole (MD) transition which is independent of local symmetry [ 73 ]. However, 5 D 0 → 7 F 2 is strongly influenced by the environment of europium ions and this electric dipole (ED) transition is said to be a hypersensitive transition [ 74 ]. For that reason, the ratio of the 5 D 0 → 7 F 2 to 5 D 0 → 7 F 1 transitions informs us about local asymmetry around the Eu 3+ ions in the glass host.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, previously published results proved that the presence of modifier oxides has an important influence on the structural, thermal, and spectroscopic properties of low phonon glass systems containing rare-earth ions. [25][26][27] Among metal oxides that are components of glasses emitting NIR luminescence, titanium(IV) oxide (TiO 2 ) deserves particular attention. 28,29 The addition of TiO 2 increases the linear and non-linear refractive indices, increasing the radiative transition probabilities and improving the non-linear optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previously published results proved that the presence of modifier oxides has an important influence on the structural, thermal, and spectroscopic properties of low phonon glass systems containing rare‐earth ions 25–27 . Among metal oxides that are components of glasses emitting NIR luminescence, titanium(IV) oxide (TiO 2 ) deserves particular attention 28,29 .…”
Section: Introductionmentioning
confidence: 99%